Synthesis of 2,9-Diethynylanthracene Derivatives - Toyota, Shinji; Kawakami, Takahiro; Iwanaga, Tetsuo (Synthesis, 2014)
New fluorescent 2,9-diethynylanthracene derivatives ethynylated at unsymmetrical positions were synthesized. The addition of a (trialkylsilyl)ethynyllithium to 2-chloro-9-anthrone gave the corresponding 2-chloro-9-ethynylanthracene, and subsequent nickel-catalyzed coupling with a (trialkylsilyl)ethynyl Grignard reagent furnished the disilylated derivatives. These compounds were used for the synthesis of various 2,9-bis(phenylethynyl)anthracenes and dianthrylbutadiynes. UV–vis and fluorescence spectra were measured to evaluate the substituent effects on the absorption and emission bands.
Keywords: alkynes; anthracenes; Kumada–Tamao coupling; Sonogashira coupling; spectroscopy